The Effect of Shearing Force that Influences Structural Transitions in Silk Fibroin (Journal of Fiber Bioengineering and Informatics, 2018)
Silk hydrogel has been utilized to deliver drug and growth factor and replace tissue. Therefore, exploring the structural changes of silk fibroin for variety of applications has attracted public concern. It has been reported that gel transition is influenced by temperature, pH, and shearing force. In this paper, we have studied the effect of shearing force that influences silk fibroin structural transitions. After stirring the silk fibroin solution at various shearing rates, the gelation time was observed. To investigate the effect of shearing force during the process, the molecular conformation of gel was investigated by CD, XRD, FT-IR and Raman spectroscopy. It was found that shearing force accelerated the gel rate, and with the increase of rate, gelation time decreased. The rate of 150r/min was more effective to promote gelation. β-sheet structure was formed by the shearing force, which was observed by X-ray diffraction. The crystallinity was increased effectively. After being lyophilized, the sample exhibited network and sponge-like structures. Remarkable changes in porosity were observed after using different shearing rates. It was observed that the higher the shearing rate, the lesser the pores formed.
Keywords: Shearing force; gel; structural transition; regenerate; silk fibroin